2019
DOI: 10.1101/636688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adrenergic-melatonin heteroreceptor complexes are key in controlling ion homeostasis and intraocular eye pressure and their disruption contributes to hypertensive glaucoma

Abstract: AbstractMelatonin regulates intraocular pressure (IOP) whose increase leads to glaucoma and eye nerve degeneration. Aiming at elucidating the role of melatonin receptors in humour production and IOP maintenance, we here demonstrate that glaucoma correlates with disassembly of α1-adrenergic/melatonin receptor functional units in cells producing the aqueous humour. Remarkably, α1-adrenoceptor-containing complexes do not coupled to the cog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 54 publications
(38 reference statements)
3
8
0
Order By: Relevance
“…Thus, activation of these receptors leads to a decrease in cytosolic cAMP levels. We have confirmed that this is the case in single transfected cells (Appendix A Figure A1B,C; see also our recent report [52]), thereby reproducing data reported in References [34,53]. HEK-293T cells expressing D 3 R or MT 1 and incubated with the selective agonists, 7-OH-PIPAT for D 3 and melatonin for MT 1 , led to significant decreases in the forskolin-induced cytosolic cAMP levels.…”
Section: Functional Characterization Of D 3 -Mt 1 Heteroreceptor Compsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, activation of these receptors leads to a decrease in cytosolic cAMP levels. We have confirmed that this is the case in single transfected cells (Appendix A Figure A1B,C; see also our recent report [52]), thereby reproducing data reported in References [34,53]. HEK-293T cells expressing D 3 R or MT 1 and incubated with the selective agonists, 7-OH-PIPAT for D 3 and melatonin for MT 1 , led to significant decreases in the forskolin-induced cytosolic cAMP levels.…”
Section: Functional Characterization Of D 3 -Mt 1 Heteroreceptor Compsupporting
confidence: 90%
“…When cytosolic cAMP levels were analyzed in the cells treated with 0.5 µM forskolin, the D 3 R agonist 7-OH-PIPAT, in agreement with the heteromer's print identified in the HEK-293T cells, did not produce any effect (Figure 4A,D). Interestingly, and as previously described by Alkozi et al, [34], none of the melatonin receptor agonists, melatonin or IIK7, were able to decrease cAMP levels in these cells. Next, we analyzed ERK1/2 phosphorylation, which was significantly enhanced when 7-OH-PIPAT was added ( Figure 4B,E).…”
Section: Detection and Functional Characterization Of D 3 -Mt 1 And Dsupporting
confidence: 80%
See 2 more Smart Citations
“…In brief the MT1 receptor is expressed in the muscle cells and melatonin acts via Gq and not via Gi; however, the involvement of the receptors in the Gq-mediated effects is dubious as the conditions of the assays are not standard from a pharmacological point of view. In this regard, activation of melatonin receptors in a heterologous expression system does not lead to immediate Ca 2+ mobilization as it occurs in the case of other GPCRs that are coupled to Gq (31).…”
Section: Introductionmentioning
confidence: 99%